Explaining Entrepreneurial Intentions in Higher Education: The Influence of Career Maturity, Self-Actualization Needs, and Entrepreneurial Mindset - Agus Noor Murfa; Muhammad Rakib; Hajar Dewantara (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze and find a model of the relationship between career maturity, self-actualization, and entrepreneurial mindset to entrepreneurial intentions among students of the Entrepreneurship Study Program, Faculty of Economics and Business, State University of Makassar. The technique used in this research is quantitative design with surveys. This research was carried out in the Entrepreneurship Study Program, Faculty of Economics and Business, State University of Makassar with a total of 420 students from 2020 to 2024. The determination of the 205 samples was carried out using proportional random samples. Data collection methods that use questionnaire tools are disseminated through Google Forms. Furthermore, the collected data was analyzed by the PLS SEM analysis method and SmartPLS analysis software version 4. The results of the research found that (1) career maturity and self-actualization have a favorable impact on entrepreneurial mindset, (2) career maturity and self-actualization have a favorable impact on entrepreneurial intentions, (3) entrepreneurial mindset has a favorable impact on entrepreneurial intentions, and (4) career maturity and self-actualization have a beneficial impact on entrepreneurial intentions through entrepreneurial mindset.